2019
DOI: 10.3390/ijms20215510
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cancer Resistance via Multifunctional Gold Nanoparticles

Abstract: Resistance to chemotherapy is a major problem facing current cancer therapy, which is continuously aiming at the development of new compounds that are capable of tackling tumors that developed resistance toward common chemotherapeutic agents, such as doxorubicin (DOX). Alongside the development of new generations of compounds, nanotechnology-based delivery strategies can significantly improve the in vivo drug stability and target specificity for overcoming drug resistance. In this study, multifunctional gold n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Chemotherapy serves an important role in the treatment of lung cancer; however, even the most effective chemotherapy has only a 30-50% response rate (20). Drug resistance of tumor cells has become an increasingly prominent setback during chemotherapy, as it severely limits Forward Reverse Amplification product length, bp LC3B ATTTCATCCCGAACGTCTCCT GCGCTTACAGCTCAATGCTAA 161 Beclin-1 GAGATACCGACTTGTTCCTTACG CTCGCCTTTCTCAACCTCTTCTT 184 GAPDH GGACCTGACCTGCCGTCTAG GTAGCCCAGGATGCCCTTGA 100 LC3B, microtubule associated protein 1 light chain 3 β. the efficacy of chemotherapeutic drugs, which in turn has meant that drug resistance has been the focus of an increasing amount of studies (21). Multiple studies have reported that autophagy may be involved in chemotherapeutic resistance developed in lung cancer (20,(22)(23)(24)(25), and that inhibiting autophagy may reduce resistance and enhance the efficacy of chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy serves an important role in the treatment of lung cancer; however, even the most effective chemotherapy has only a 30-50% response rate (20). Drug resistance of tumor cells has become an increasingly prominent setback during chemotherapy, as it severely limits Forward Reverse Amplification product length, bp LC3B ATTTCATCCCGAACGTCTCCT GCGCTTACAGCTCAATGCTAA 161 Beclin-1 GAGATACCGACTTGTTCCTTACG CTCGCCTTTCTCAACCTCTTCTT 184 GAPDH GGACCTGACCTGCCGTCTAG GTAGCCCAGGATGCCCTTGA 100 LC3B, microtubule associated protein 1 light chain 3 β. the efficacy of chemotherapeutic drugs, which in turn has meant that drug resistance has been the focus of an increasing amount of studies (21). Multiple studies have reported that autophagy may be involved in chemotherapeutic resistance developed in lung cancer (20,(22)(23)(24)(25), and that inhibiting autophagy may reduce resistance and enhance the efficacy of chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, several different applications of AuNPs as carriers in cancer therapy have been described [17,[160][161][162]. Indeed, AuNPs functionalized with novel drugs/compounds have been described to increase drug efficacy and tumor reduction [49,160,163,164]. Recently, Coelho et al developed a drug delivery nanosystem based on pegylated AuNPs loaded with doxorubicin and varlitinib, an anthracycline and a tyrosine kinase inhibitor respectively, for a combined approach against pancreatic cancer cells [165].…”
Section: Metallic Nanoparticlesmentioning
confidence: 99%
“…Nevertheless, perhaps the most used metallic nanoparticles for gene therapy have been based on gold. In fact, AuNPs have been described as specific and efficient carriers, used in target-specific delivery of RNAi (e.g., siRNA, miRNA, shRNA), alone or in combination with drugs or antibodies, for example [91,92]. In fact, AuNPs have been used as theranostic systems in cancer, due to their biocompatibility and unique physico-chemical properties, including their optical behavior derived from the localized surface plasmon resonance (SPR).…”
Section: Metal Nps For Gene Silencingmentioning
confidence: 99%